2017
DOI: 10.1590/1983-21252017v30n125rc
|View full text |Cite
|
Sign up to set email alerts
|

Tests for the Selection of Forage Turnip Progeny to Order the Vigor and Longevity of Seeds

Abstract: -Forage turnip (Raphanus sativus L. var. oleiferus Metzg.) progeny with seeds of higher physiological quality are of importance for farmers and seed producing companies. The objective of this work was to identify tests to be used in laboratories for the selection of turnip progeny having seeds of higher germination, vigor, seedling emergence in the field, and storage potential. Seeds of 100 turnip progeny of paternal half-sibs were evaluated as to water content, 1,000-seed mass, first count of the standard ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Genetic materials with low initial vigor would be more affected by classification of seed by size, as was probably the case of Portuguesa Cultivar. Vigor is not only influenced by the morphological and physiological characteristics of seeds, because genotype can also affect the physiological quality (Oliveira, Martins, Pereira, Lopes, & Torres, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic materials with low initial vigor would be more affected by classification of seed by size, as was probably the case of Portuguesa Cultivar. Vigor is not only influenced by the morphological and physiological characteristics of seeds, because genotype can also affect the physiological quality (Oliveira, Martins, Pereira, Lopes, & Torres, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Similar heritability results were observed in studies with: i) seeds from three cultivars and fourteen lineages of soybean that were selected for germination and seedling emergence in sandy soil from regions in Minas Gerais (Vasconcelos et al, 2012); ii) 94 bean lineages in relation to seed dry mass (Maia et al, 2011); iii) carrot half-siblings for the first germination count, germination, and accelerated aging tests (Martins et al, 2014); and iv) for forage turnip seeds in relation to germination, seedling vigor classification, accelerated aging test, seedling emergence in the field (S. S. C. Oliveira et al, 2014), and seedling emergence speed index in the field (S. S. C. Oliveira et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Research evaluating germination and seed vigor (e.g., germination first count, germination, accelerated aging tests, emergence of seedlings in the field, and storage potential) has indicated that breeding programs combined with selection methods based on the index theory can improve the quality of seeds (Maia, Silva, Ramalho, & Abreu, 2011;Vasconcelos, Reis, Sediyama, & Cruz, 2012;Machado, 2014;S. S. C. Oliveira, Martins, Cruz, & Silva, 2014;S. S. C. Oliveira, Pereira, Lopes, & Torres, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation